Restriction endonuclease mapping of bacteriophage phi105 and closely related temperate Bacillus subtilis bacteriophages rho10 and rho14. - Perkins, J B (1978)
Cleavage maps of the three similar Bacillus subtilis temperate bacteriophages, phi105, rho10, and rho14, were constructed by partial digestion analysis utilizing the restriction endonuclease EcoRI. Comparison of the topography of these maps indicates that all phage DNAs posses cohesive ends and a number of EcoRI restriction sites; the fragments are conserved, and the estimated base substitution/nucleotide divergence between these phages is 0.03 to 0.07 based on conserved fragments or between 0.03 and 0.11 based on conserved cleavage sites. These lines of evidence indicate that phi105, rho10, and rho14 are closely related. Double-enzyme digestion analysis reveals that rho14 DNA has unique SalGI and BglII restriction sites and phi105 DNA has a unique SalGI restriction site, making these phages possible cloning vectors for B. subtilis.